Unlocking renewable energy potential: Overcoming knowledge sharing hurdles in rural EU regions on example of poland, sweden and france - Justyna Żywiołek; Radosław Wolniak; Wieslaw Wes Grebski; Sunil Tiwari; Marek Matuszewski; Adam Koliński (PLoS ONE, 2025)
The optimal technological choice for sustainable development lies in renewable energy sources (RES). However, the potential offered by RES utilization poses significant challenges for mobile technologies and everyday living. Despite extensive research and information highlighting the benefits of renewable energy, there remains considerable debate, and limited awareness persists. The advantages of RES are not fully comprehended, raising concerns about its consistent application. Regrettably, lack of knowledge and a fundamental understanding hinders effective dissemination. To gauge the attitudes of residents in regions where RES is employed, this study employed a questionnaire authored by the researcher. The study was conducted between June 2022 and January 2023, with a total of 12,428 participants completing the survey. The sampling method utilized an online form distributed via various social media channels and among local contacts of the authors in Poland, Sweden, and France. Gender allocation: 58% male and 42% female. Respondents shared their perspectives on ecology and disclosed their familiarity with RES utilization. Results indicate public skepticism regarding the adequacy of RES security measures and the level of knowledge for its effective use. Insufficient experts, limited social advocacy, and reliance on online sources contribute to a low level of awareness. In several EU countries, the absence of widely accepted and easily accessible information on renewable energy sources (RES) hinders knowledge sharing and adoption. Despite the EU’s efforts to promote renewable energy through directives and subsidies, rural communities in these countries often lack adequate education and awareness about RES technologies. This gap in knowledge contributes to unfavorable perceptions, with some residents viewing renewables as unreliable or economically unfeasible options compared to traditional energy sources like coal or natural gas. Additionally, bureaucratic hurdles and inconsistent government policies further complicate the transition to renewable energy, discouraging investment and innovation in the sector. As a result, while the EU aims for a sustainable energy future, these barriers impede the widespread growth of RES and hinder progress towards climate targets. In Poland the study found that 76% of respondents expressed favorable perceptions of RES, indicating a general inclination towards adopting clean energy solutions. In Sweden, the analysis uncovered a high level of environmental awareness among participants, with 85% of respondents expressing concern about environmental degradation. Despite this awareness, 62% of participants reported reservations about the security and affordability of energy derived from renewable sources. Additionally, 48% of respondents expressed uncertainty or ambivalence regarding the environmental benefits of RES. In France, the research revealed similar concerns among respondents regarding the security and affordability of renewable energy. 59% of participants expressed reservations about the security of energy derived from renewable sources, while 53% cited perceived high costs as a barrier to adoption. Furthermore, 41% of respondents identified underdeveloped RES infrastructure as a hindrance to wider acceptance and utilization. The quantitative data highlights the complex landscape of renewable energy perceptions and attitudes in Poland, Sweden, and France. While there is a general awareness of environmental issues and a positive inclination towards clean energy solutions, concerns about security, affordability, and infrastructure remain significant barriers to widespread adoption. These findings underscore the importance of targeted interventions and educational efforts to address these challenges and promote sustainable energy practices across Europe. Renewable energy sources (RES) represent a critical avenue for sustainable development, offering a pathway to mitigate environmental degradation and reduce dependence on fossil fuels. This study investigates public attitudes, knowledge levels, and barriers to RES adoption in rural areas of Poland, Sweden, and France, highlighting the unique socio-economic and cultural factors influencing these regions. Conducted between June 2022 and January 2023, the research utilized an online survey, gathering responses from 12,428 participants across these countries. Respondents evaluated statements on environmental responsibility, RES knowledge and application, and perceived obstacles, using a five-point Likert scale. Key findings reveal that while environmental awareness is high, significant barriers persist in the form of limited knowledge, underdeveloped infrastructure, and perceptions of high costs associated with RES. In Poland, 76% of respondents expressed a positive view of RES but cited concerns about cost and security. Swedish participants demonstrated strong environmental awareness (85%), yet 62% voiced reservations about RES affordability and reliability. French respondents similarly highlighted concerns regarding infrastructure and costs, with 41% identifying underdeveloped RES systems as a primary hindrance. The study underscores the importance of targeted educational campaigns and policy interventions to bridge knowledge gaps and foster greater acceptance of RES. Tailored strategies addressing local barriers—such as financial incentives, community-based advocacy, and infrastructure investments—are essential to overcoming these challenges. By exploring diverse perspectives and barriers across the three countries, this research contributes valuable insights to the broader discourse on sustainable energy transitions in the EU.